Eklesiologi Keindonesiaan: Partisipasional, Inkarnasional, Relasional - Takdare, Jerry Paulus; Batlajery, Agustinus M.L; Ruhulessin, Johni Chr (Program Pascasarjana UKIM, 2024)
This article proposes the communion, sharing, together, and gandong models as a new approach that the church can use for interacting in the public spaces of the national and religious in Indonesia. This model is an implication of three important concepts: participational, incarnational, and relational, as such, it becomes an alternative to the unity-equality model as proposed by John Titaley and the exemplary model as proposed in the thought of Eka Darmaputera. By discussing with Titaley and Darmaputera, the author demonstrates that participational, incarnational, and relational must be formulated and constructioned in the ecclesiological (theology) of the churches in Indonesia to show the essence and mission of the Trinity God in their ecclesial-social life. This research indicates that communion, sharing, together, and gandong models provide a wide space to show the church's identity as belonging to the Trinity God and, simultaneously, with the others to enrich life together as a nation of Indonesia.